(untitled) (International journal of artificial intelligence, 2026)
This article provides an in-depth scientific analysis of financial relations in service sector enterprises under modern economic conditions. The study examines the role of the service sector in the economy, the structure of financial flows, and the relationship between revenues and expenditures based on recent statistical data.